Chalcone-analogue fluorescent prfobes for saccharides signaling using the boronic acid group - DiCesare, Nicolas (Tetrahedron Lett, 2002)
Two new fluorescent probes based on 1,3-diphenylprop-2-en-1-one and on 1,5-diphenylpenta-2,4-dien-1-one structures are presented. Both probes posses one electron-donating dimethylamino group and one boronic acid group (electron-withdrawing group). The change between the neutral and the anionic form of the boronic acid group induced at high pH and/or in presence of sugar, induces optical changes for both probes. Spectroscopic data, pK(a) and dissociation constants for different monosaccharides are presented and discussed in terms of sugar detection.